2022
DOI: 10.3390/genes13030495
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Multigenic Protein-Altering Variant Frequency in Familial Exudative Vitreo-Retinopathy (FEVR) Patients by Targeted Sequencing of Seven FEVR-Linked Genes

Abstract: While Inherited Retinal Diseases (IRDs) are typically considered rare diseases, Familial Exudative Vitreo-Retinopathy (FEVR) and Norrie Disease (ND) are more rare than retinitis pigmentosa. We wanted to determine if multigenic protein-altering variants are common in FEVR subjects within a set of FEVR-related genes. The potential occurrence of protein-altering variants in two different genes has been documented in a very small percentage of patients, but potential multigenic contributions to FEVR remain unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The Eg5-associated disease represents a potential system ciliopathy with defects in photoreceptor development and retinal angiogenesis [ 22 , 46 ]. The Eg5 vascular endothelial cell-specific knockout mouse models suggest that the Eg5 -deficient retinal vascular phenotype is independent of the established Norrin Wnt β-catenin signaling pathway [ 54 , 55 ]. In this study, we have demonstrated that Eg5 inhibition results in cell apoptosis in the eye, which further contributes to the disorganization of retinal cells and cell layers.…”
Section: Discussionmentioning
confidence: 99%
“…The Eg5-associated disease represents a potential system ciliopathy with defects in photoreceptor development and retinal angiogenesis [ 22 , 46 ]. The Eg5 vascular endothelial cell-specific knockout mouse models suggest that the Eg5 -deficient retinal vascular phenotype is independent of the established Norrin Wnt β-catenin signaling pathway [ 54 , 55 ]. In this study, we have demonstrated that Eg5 inhibition results in cell apoptosis in the eye, which further contributes to the disorganization of retinal cells and cell layers.…”
Section: Discussionmentioning
confidence: 99%
“…One such recent example was reported by our group recently, Cys450Ter, a nonsense variant that generates an early termination codon within TM helix-6. This was predicted to result in the loss of TM helix-7 and the C-terminal PDZ-binding domain of the FZD4 protein [17].…”
Section: Fzd4mentioning
confidence: 99%
“…Norrie disease, Coats disease, retinopathy of prematurity (ROP), and familial exudative vitreoretinopathy (FEVR) belong to a family of rare retinopathies that are characterized by irregular vascularization or even lack of vascularization of the retina [16]. Our group has contributed to continuing efforts to identify variants in several genes that play a role in the pathogenesis of these diseases, which include NDP, FZD4, TSPAN12, and LRP5, members of the canonical Norrin Wnt-signaling pathway [17]. Recent studies have also uncovered additional genes, some that have no direct participation in the Norrin-signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norrie disease, Coats disease, retinopathy of prematurity (ROP) and familial exudative vitreoretinopathy (FEVR) belong to a family of rare retinopathies that are characterized by irregular vascularization or even lack of vascularization of the retina [11]. Our group has contributed to continuing efforts to identify variants in several genes that play a role in the pathogenesis of these diseases, which include NDP, FZD4, TSPAN12, and LRP5, members of the canonical Norrin Wnt-signaling pathway [12]. Recent studies have also uncovered additional genes, some that have no direct participation in the Norrin-signaling pathway.…”
Section: Introductionmentioning
confidence: 99%